Articles of Agreement. (International Monetary Fund, 2016)
This paper discusses the Second Amendment of the IMF's Articles of Agreement. The drafting of the Second Amendment of the Articles of Agreement was a more prolonged and more complicated task than the preparation of the First Amendment. One characteristic of the Second Amendment is the transformation into law, by incorporation in the Articles, of policies that the IMF had adopted over the years. The provisions of the Second Amendment that deal with repurchase obligations, the selection of currencies for use in purchases and repurchases, and stand-by arrangements are among the many examples that are sometimes referred to as constituting the modernization of the IMF.